2019
DOI: 10.1038/s41419-019-1830-8
|View full text |Cite|
|
Sign up to set email alerts
|

Excess hepsin proteolytic activity limits oncogenic signaling and induces ER stress and autophagy in prostate cancer cells

Abstract: The serine protease hepsin is frequently overexpressed in human prostate cancer (PCa) and is associated with matrix degradation and PCa progression in mice. Curiously, low expression of hepsin is associated with poor survival in different cancer types, and transgenic overexpression of hepsin leads to loss of viability in various cancer cell lines. Here, by comparing isogenic transfectants of the PCa cell line PC-3 providing inducible overexpression of wild-type hepsin (HPN) vs. the protease-deficient mutant HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…Nonetheless, the generated data displayed the involvement of HPN in the metastatic progression of CRC. One of the plausible explanations was that overexpression of HPN was associated with matrix degradation (invasion and metastasis initiator), similar to that of prostate cancer [ 86 ]. Another assumption was that HPN was strongly associated with pathogenesis and early carcinogenesis of CRC, since it caused disorganization of the basement membrane and promoted primary prostate cancer progression and metastasis to liver, lung, and bone [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the generated data displayed the involvement of HPN in the metastatic progression of CRC. One of the plausible explanations was that overexpression of HPN was associated with matrix degradation (invasion and metastasis initiator), similar to that of prostate cancer [ 86 ]. Another assumption was that HPN was strongly associated with pathogenesis and early carcinogenesis of CRC, since it caused disorganization of the basement membrane and promoted primary prostate cancer progression and metastasis to liver, lung, and bone [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“… 41 Willbold et al demonstrated that the proteolytic activity of hepsin is related to ER stress and autophagy in prostate cancer cells. 8 An inhibitor of hepsin was reported to block prostate cancer bone metastasis. 9 Here, we show that hepsin is overexpressed in prostate cancer and that hepsin knockdown inhibits cell invasion and EMT in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Hepsin is frequently overexpressed in PC 5 , 6 and correlated positively with aggressiveness. 7 The functions of hepsin in malignant biological behaviors, including autophagy, 8 bone metastasis 9 and tumor growth, 10 of PC have been well studied. Hepsin is also involved in the diagnosis and prognosis of PC.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of hepsin-mediated mechanisms have been proposed in cancer. These include pro-HGF and promacrophage stimulating protein activation to enhance Met and RON signaling, respectively [42,54,56,118]; activation of metalloproteinases to promote matrix protein degradation [119,120]; activation of other cell surface proteases, which in turn enhance receptor-mediated signaling [39,121]; depletion of HAI-1 that blocks the cancer-promoting activity of other cell surface proteases [56,122,123]; direct cleavage of matrix proteins and cell surface receptors [62,124,125]; induction of ER stress and the unfolded protein response [126]; and deregulation of cell cycle and apoptotic signaling [127]. More detailed discussions regarding hepsin and associated mechanisms in cancer are covered in recent comprehensive reviews [34,37,38].…”
Section: Hepsin In Cancermentioning
confidence: 99%